2016
DOI: 10.1136/bmjqs-2015-004697
|View full text |Cite
|
Sign up to set email alerts
|

When doctors share visit notes with patients: a study of patient and doctor perceptions of documentation errors, safety opportunities and the patient–doctor relationship

Abstract: Despite concerns about errors, offending language or defensive practice, transparent notes overall did not harm the patient-doctor relationship. Rather, doctors and patients perceived relational benefits. Traditionally more vulnerable populations-non-white, those with poorer self-reported health and those with fewer years of formal education-may be particularly likely to feel better about their doctor after reading their notes. Further informing debate about OpenNotes, the findings suggest transparent records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
167
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 39 publications
12
167
3
4
Order By: Relevance
“…In this study, they were the most common source of potential safety concerns reported by patients, perhaps preventing some harms. In general, reading notes may increase trust between patients and doctors,11 and transparent communication about mistakes nurtures better relationships, a key factor in lawsuits 43–45…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, they were the most common source of potential safety concerns reported by patients, perhaps preventing some harms. In general, reading notes may increase trust between patients and doctors,11 and transparent communication about mistakes nurtures better relationships, a key factor in lawsuits 43–45…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that 26% of primary care physicians believe patients would find non-trivial errors in their notes,11 that up to 60% of EHRs contain at least one error,12 that 43% of medications in the EHR may be inaccurate13 and that the mismatch rate between the medications patients take and those listed in the medical record may be as high as 95% 14…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Options include use of a nursing pool followed by distribution of messages to LIPs as needed or vice versa. Although evidence thus far has not shown a great increase in patient calls following the implementation of shared notes, 3 anecdotally, providers' experiences have varied. Practice effects may differ based on patient population and practice size and a practice should be prepared to receive an increased volume of communication.…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…This issue of BMJ Quality & Safety features a paper by Bell et al 1 that follows up on the original ‘Open Notes’ experiment with providing patients electronic access to their primary care providers' notes. In the first report,2 the intervention was well received by the patients and did not provoke the anticipated adverse impacts feared by physicians.…”
mentioning
confidence: 99%